2013
DOI: 10.1353/hsj.2013.0026
|View full text |Cite
|
Sign up to set email alerts
|

Student Use of Aspirational and Linguistic Social Capital in an Urban Immigrant-Centered English Immersion High School

Abstract: Expanding upon Yosso’s theory of community cultural wealth , this interview-based qualitative study finds that Mexican youth in an urban two-year English immersion high school here referred to as Literacy High are assisted academically by what Yosso would call their aspirational capital and what the present article theorizes as their linguistic social capital , or their ability to utilize a Spanish-speaking student network to understand assignments and instructions. Among these students, opinions regarding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…In addition, the faculty members taught intellectual and social skills through various styles and languages, which contributed to students’ linguistic capital (Alphonse, 2010; Yosso, 2005). The students perceived that college administration and faculty members were part of their support system, like a family to them (Straubhaar, 2013). Students also noted that positive and caring faculty members inspired them to believe in themselves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the faculty members taught intellectual and social skills through various styles and languages, which contributed to students’ linguistic capital (Alphonse, 2010; Yosso, 2005). The students perceived that college administration and faculty members were part of their support system, like a family to them (Straubhaar, 2013). Students also noted that positive and caring faculty members inspired them to believe in themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Students’ experiences with the CCs indicated that they perceived the college as planning program and curricular goals to support and benefit the students’ skills, aptitudes, and attitudes. The investment in cultural capital, preentry attributes, goals, and commitment contributed to high persistence and determination, which is essential to success in college (Sandoval-Lucero, Maes, & Klingsmith, 2014; Straubhaar, 2013; Yosso, 2005). The findings revealed that the faculty members’ engagement with students contributed to strong social integration (Soria & Stebleton, 2012; Tinto, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Dayana's recall of the self-regulation strategies improves, and she can draw from her experiences of communicating in Spanish with family living in Venezuela to build upon the knowledge gained. Common linguistic roots are a source immigrant-origin students use to find social and academic support networks (Straubhaar, 2013). In Straubhaar's (2013) qualitative study, newcomer immigrant-origin students with varying degrees of English proficiency reported using their heritage language with immigrant-origin peers to help one another understand the concepts learned in their classes.…”
Section: Linguistic Capitalmentioning
confidence: 99%
“…For adolescent newcomers and their families, cultural capital may be defined as the meanings, knowledge, customs, achievements, and outlooks that are related to their social positions. Often, the focus of school practitioners and policy makers is defining what students lack and what their needs are (Straubhaar, 2013). In the case of newcomers, the focus remains on building English proficiency.…”
Section: Building Capital: An Overview Of the Literaturementioning
confidence: 99%
“…Despite the importance of social and cultural capital to newcomers' success, many schools seem to limit their schooling experiences to the remediation of English language proficiency (Estrada, 2014;Kanno, 2018;Alogali, 2018;Kustati & Al-Azmi, 2018). There remains a significant lack of comprehensive policies that address the structural, economic, and linguistic factors for newcomers to build the necessary capital while in school, [capital] which could lead to building post-secondary economic capital and to equal participation in U.S. education (Noguera, 2004;Straubhaar, 2013;Tang, 2015).…”
Section: Introductionmentioning
confidence: 99%